Intertwined risk factors of mental health and cardiovascular diseases: A cross-sectional survey in Godawari Municipality of Far-western Nepal - Ramesh Ojha; Chiranjivi Adhikari; Hari Prasad Kaphle; Dikshya Adhikari (PLoS ONE, 2025)
Introduction Cardiovascular diseases (CVDs) are the leading global cause of death, whereas mental disorders account for one-third of all global disabilities. Despite clear available evidence of a significant relationship between the CVDs and mental disorders, and the CVDs being regressional to certain risk factors, they are less explored in the Nepalese context, especially for mental disorders. Hence, we aimed to determine the prevalence of mental health status and its associated factors among people with cardiovascular risk status. Methods A community-based study was carried out during Sep-Nov 2024 among 390 people aged 30–69 years with cardiovascular risk status in Godawari Municipality, Kailali. Data were collected with face-to-face interviews using structured questionnaires consisting of four sections: a) socio-demographic characteristics; b) CVD risk factors; c) mental health status; and d) anthropometric measurements, using the KoboToolbox, a mobile and computer-based application. Further, we imported data into SPSS software for statistical analysis. We presented categorical variables as frequency and percentage and continuous variables as median and quartiles. We applied univariate and multivariate logistic regression to determine factors associated with depression symptoms, anxiety, and stress. The result of logistic regression was presented as crude odds ratio, adjusted odds ratio (AOR), beta coefficients (β), their 95% confidence interval, and p-values. Results Of 390 participants, females were two-thirds (67%), and the median age was 48 (36 ~ 60). The prevalences of depression, anxiety, and stress symptoms were found to be 47.2%, 62.3% and 55.1%, respectively. From multivariate logistic regression analysis, depression symptoms were positively associated with females (β = 1.002, p < .001) and the presence of one CVD risk factor (β = 1.082, p = .016), two risk factors (β = 1.362, p = .006) and three or more risk factors (β = 1.720, p = .017). Anxiety symptoms were associated with exposure to secondhand smoking (β = 0.725, p = .024) and the presence of one risk factor (β = 1.548, p < .001), two risk factors (β = 1.734, p < .001) and three or more risk factors (β = 1.852, p = .022). Dalit, Janajati and Madhesi (β = 0.735, p = .026) and the presence of one risk factor (β = 1.811, p = .001), two risk factors (β = 2.054, p = .016) and three or more risk factors (β = 2.138, p < .001) were associated with stress symptoms. All three mental disorders were found to worsen as the number of CVD risk factors increased. Conclusion The study revealed that nearly fifty percent of the prevalence of each of depression, anxiety, and stress symptoms among people with cardiovascular risk status. Mental health screening is suggested among the people with CVD risk factors, additionally considering female, secondhand smoker, and disadvantaged ethnic populations for depression, anxiety, and stress, respectively. Further, a validation study is recommended for accuracy and yield.